2010
DOI: 10.1111/j.1365-2486.2010.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical modeling of abiotic and biotic factors controlling ecosystem respiration across eddy covariance sites

Abstract: In this study we examined ecosystem respiration (RECO) data from 104 sites belonging to FLUXNET, the global network of eddy covariance flux measurements. The goal was to identify the main factors involved in the variability of RECO: temporally and between sites as affected by climate, vegetation structure and plant functional type (PFT) (evergreen needleleaf, grasslands, etc.). We demonstrated that a model using only climate drivers as predictors of RECO failed to describe part of the temporal variability in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
140
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 92 publications
5
140
1
Order By: Relevance
“…From these findings, researchers have gradually recognized that GPP and RE are not independent, but are two strongly associated ecological processes. RE is strongly coupled with GPP across timescales (Dunn et al, 2007;Migliavacca et al, 2011). For example, RE follows the same dynamic patterns as GPP from daily to seasonal scales (Krishnan et al, 2009; et al, 2011; Thomas et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…From these findings, researchers have gradually recognized that GPP and RE are not independent, but are two strongly associated ecological processes. RE is strongly coupled with GPP across timescales (Dunn et al, 2007;Migliavacca et al, 2011). For example, RE follows the same dynamic patterns as GPP from daily to seasonal scales (Krishnan et al, 2009; et al, 2011; Thomas et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…6b). Previous studies also indicated that reference respiration depends strongly on mean annual GPP (e.g., Yuan et al, 2011), and can be estimated by LAI max (e.g., Migliavacca et al, 2011) or mean annual springtime EVI (e.g., Jägermeyr et al, 2014).…”
Section: Characteristics Of the Model Parametersmentioning
confidence: 99%
“…However, it is important to understand that the tight coupling between GPP and R eco in most ecosystems (Irvine et al, 2008;Mahecha et al, 2010;Migliavacca et al, 2010;van der Molen et al, 2011;Peichl et al, 2013;Rambal et al, 2014) complicates systematic assessments across sites. For example, heterotrophic respiration is not only a function of the environment, but is also strongly driven by the availability of recently assimilated carbon (Irvine et al, 2005;Granier et al, 2007;Ruehr et al, 25 2012).…”
mentioning
confidence: 99%